PENGARUH ECONOMIC VALUE ADDED DAN MARKET VALUE ADDEDTERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - Rizky Alika Ramadhani; Emma S.N. Sipayung (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
The objective of study is determine the influence of EVA and MVA to stock returns in manufacturing companies listed on the Indonesian Stock Exchange from 2011 until 2013. Based sampling technique using a :purposive sampling” obtained sample of 91 companies and number of observations as many as 264. The number of observations in thisstudy using multiple regression analysis with the spss 20.0 to analyze data.The results of the study shows that EVA variable has positive effects on stock returns. But other result shows the variable MVA has negative effects on stock returns.